THE ADHESIVE PROPERTY OF ENTEROCOCCUS WHICH WERE ISOLATED FROM TROPHIC ULCER CONTENTS OF PANCREATIC DIABETES PATIENTS - Peretyatko, E.G. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Results of study of Enterococcus stem microorganisms which were isolated from trophic ulcers of pancreatic diabetes patients adhesive properties in comparison  with intestinal strain of enterococcus are produced in the paper. It was established that enterococcus defined high-adhesive properties. It was achieved that range of evidence of adhesive abilities of microorganisms taken in the experiment depended on availability of purulent septic process.